The bell tolls for the relationship between house dust mite exposure and asthma in childhood - Catarina Almqvist; Guy Marks; Qiang Li; Daniel Crisafulli; Euan Tovey (European Respiratory Review, 2008)
Prior evidence has suggested a direct relationship between the level of house dust mite (HDM) allergen exposure, sensitisation and asthma. A recent cross-sectional study indicated a bell-shaped relationship between HDM exposure and sensitisation [1]. We examined the effects of cumulative HDM allergen exposure during the first 5 years of life on outcomes at age 5 years in Sydney, a high HDM environment. In the Childhood Asthma Prevention Study, bed dust samples collected at 3, 6, 9 and 12 months and then 6-monthly (total 6615 samples) until age 5 years were analysed for HDM allergen by ELISA. At five years, 516 children were assessed for wheeze and asthma by questionnaires and spirometry, and 488 for sensitisation by skin test. Time-weighted average HDM allergen concentration was estimated for each individual. The range was divided into quintiles with cut-points being 3,5; 7,8; 13,5 and 23,4 ug Der p 1/g. The association between HDM levels and outcomes was analysed with chi-square test, adjusting for confounders. The figure shows the prevalence of outcomes by quintile of time-weighted average of HDM allergen. In this birth cohort, there is a bell-shaped dose response between HDM levels and sensitisation and asthma. This may reflect tolerance to HDM allergen or be attributable to protection from associated exposures, and prompts further research on the mechanisms.